Effects of ageing on longissimus thoracis et lumborum muscle of local beef - Chakrabartty, S; Akter, S; Murshed, HM; Rahman, MM; Azad, MAK (Meat Research, 2024)
The ageing process significantly influences the quality parameters of beef, including water holding capacity (WHC), drip loss, tenderness, pH, and cooking loss. This study aimed to investigate the impact of ageing on these parameters and establish ageing as a valuable method for enhancing beef (LTL muscle) tenderness while minimally affecting other quality attributes. Using beef samples subjected to ageing periods of 1 day, 3 days, and 7 days, and 9 days, a comprehensive analysis was conducted to assess changes in WHC, drip loss, tenderness, pH, and cooking loss over time. The research findings revealed nuanced variations in these parameters across the ageing periods. While WHC, drip loss, pH, and cooking loss exhibited minimal changes throughout the ageing process, a notable improvement in tenderness was observed with increasing ageing duration. This enhancement in tenderness underscores the effectiveness of ageing in softening beef muscle fibers and improving eating quality. Moreover, the study explored the underlying mechanisms driving the observed changes in beef quality during ageing, including proteolysis, collagen degradation, and moisture redistribution. Understanding these mechanisms is crucial for optimizing ageing conditions and maximizing the beneficial effects on beef tenderness. Overall, the findings of this study contribute to the body of knowledge on the effects of ageing on beef quality parameters and provide practical insights for meat industry professionals and stakeholders. By establishing ageing as a valuable process for enhancing beef tenderness, this research has implications for meat processing practices, product development, and consumer satisfaction.